A difusão do Open Courseware – OCW via televisão digital interativa aberta – DTVi: um estudo prospectivo - Fonte-Boa, Flávio (2019)
The digitalization of information has profoundly altered the access and distribution of valid information to the construction of knowledge, far beyond the institutional forms of its apprehension. The interactivity and diversity offered by the Internet are undoubtedly a push factor in the development of the informational platforms based on computers. In parallel evolution and organization of videos on demand, deepen the transformation of the advent of interactive DTV, which brings coherence to a future convergence of means for the platforms based on TV. This study aimed to discover the future paths for the diffusion of the Open Courseware initiative - OCW in Brazil, and worth of interviews with script by structured questionnaire in the Delphi methodology. The prospective estimates were taken from a group of experts, regarding the construction of an unrestricted access space, through interactivity tools usable in the open DTVi, to a repository of informational media content, structured in videos that induce the construction of knowledge. The insertion of this discussion in the public agenda can subsidize synergetic policies of education and communication, which guide the use of this means of national coverage and technically capable of interactivity, as effective contributor in the construction of a "Knowledge Society". This research was mainly based on the works of Jost, Orozco, Lévy and Jenkins, who among other authors, show the parallel supports to the institutional training of certifying school, revealing socio-educational advantages, in the media devices of stimulating and valuing thematic contents that promote knowledge. The prospective consultation of experts using the interview methodology in Delphi resulted in compiled text by the technique of the Collective Subject Discourse that guides a public policy for OPEN COURSEWARE - OCW with the access promoted via OPEN DTVi. The findings indicate that digital convergence amplifies the possibilities and the rationality of the viewer, preparing them for a reflexive use in other converging media spaces, and consolidates the use of the media to transform the social reality of each individual and broaden the socialization of knowledge in Brazil.